Analysis of credit cooperation in the current economic space - Dobrovol’ska, Olena (Technology audit and production reserves, 2016)
A study of possible development directions of credit cooperatives in the current challenges of economic space is conducted for effective formation. Modern credit cooperatives are the two most common types: cooperative banks (mostly in Europe) and credit unions (in most parts of the world) and are credit cooperative sector of the economies of many countries. Braking factors for development of credit cooperative are: imperfection of legislation; lack of real financial support from the state; improper control of credit unions; unprofessional administrative bodies on audits of unions and, in some cases, outright cover-up of illegal activities; formation of negative public opinion in the media; encouraging of borrowers do not repay credits; unwillingness of managers of a number of credit unions to implement the basic principles of cooperative credit activity and growth of inconformity of credit union activities with the principles of cooperation. The proposed model for developing three-level cooperative credit system in Ukraine provides phased expansion of the market mandate for credit unions in corporate lending and the provision of financial services, creation of credit cooperatives, central and local cooperative banks and other elements of the system that are addressing the whole spectrum of problems, in particular the system of guarantees and deposit insurance system to support the financial stability of credit unions, credit bureaus, centers of information technology, service infrastructure that would ensure minimizing risk and entry of credit unions in payment systems, educational infrastructure and so on.